Zdravljenje otrok z astmo z enim ali dvema dnevnima odmerkoma inhalacijskega kortikosteroida - Besednjak-Kocijančič, Lilijana (Zdravniški vestnik, 2006)
Background Inhaled corticosteroids are recommended drugs for asthma treatment.Their growth suppressive potential is well-known. Twice-daily delivery is usually used in children, but poor compliance of such long-term treatment may represent a problem which can be resolved with once-daily regimen. The aim of this prospective study was to asses the efficacy and the influence on growth of long term once-daily administration of inhaled fluticasone propionate (FP) in asthmatic Slovene children under 5 years. Methods Children with mild persistent asthma took part in parallel group trial. Their parents recorded asthma symptoms, beta2-agonist usage, and PEF using a form for asthma control on a daily basis for a period of one year. According twice or once-daily treatment they were divided in two groups: groupA - children receiving FP 100microg twice-daily and group B children receiving FP 200microg once-daily at bedtime. Mean height of 26 children of the same sex and age from each group and of 26 healthy children (groups A1, B1, C) was observed. Chi-square analysis with Yates' correction and t tests were employed for between - group analyses (SPSS software 11.0). Results FP given once-daily was as effective and tolerated as the same total dose given twice-daily. PEF, asthma symptoms and bronchodilator use of children from group B were not significantly different from those from group A (p > 0. 05). The mean height increase of children receiving FP once-daily was smaller for 0.22 cm than of children receiving FP twice-daily and for 0.98 cm than of healthy children (t = Z.56 p = 0. Z32; DF: 24). Conclusions Once-daily administration of inhaled FP in asthmatic children is safe and as effective astwice-daily administration. The suppressive potential is greater when it is given once-daily.
Keywords: Administration And Dosage; Administration, Inhalation; Asthma; Astma; Body Height; Child; Drug Therapy; Glucocorticoids, Synthetic; Glukokortikoidi umetni; inhalacije; inhalatorji; Največji, ekspiratorni pretok; otroci; Otrok; Peak Expiratory Flow Rate; rast; Telesna višina; therapy; Zdravilo, inhalacijska uporaba; zdravljenje